Going to University: The Influence of Higher Education on the Lives of Young South Africans - Adenuga, Kehinde (Journal of Interdisciplinary Studies in Education, 2021)
Going to University: The Influence of Higher Education on the Lives of Young South Africans is a great book written very well by the authors. The use of the narratives gives the book an engaging and readable quality that will make a reader to complete the reading. The authors narrated the interviews conducted with 73 young people six years after they enrolled at one of the urban schools in South Africa. As the book progresses, the authors further introduced us to 20 young people whose stories were narrated in detail.